EDUKASI GEN Z KAYA LITERASI DINI - Wahnawidya Widhianingrum; Riawan Riawan; Ranti Kurniasih (Jurnal Terapan Ekonomi dan Bisnis, 2025)
Generation Z (Gen Z), who grew up in the digital era, has extensive access to information and technology. However, ironically, their financial literacy is still relatively low. 1 Based on data from the Financial Services Authority (OJK), the level of financial literacy among young people is still below 40%. 2 Therefore, more intensive efforts are needed to educate and improve financial literacy to help them manage their finances wisely. Through the "Gen Z Rich in Literacy from an Early Age" educational program, it is hoped that partners (Gen Z) can provide a basic understanding of financial literacy. This program is expected to instill the habit of managing money wisely from an early age and become an important provision in their future lives. Partners in this community service activity are students of the Management Study Program at Muhammadiyah University of Ponorogo with a total of 20-30 participants. These students come from various semester levels and have academic backgrounds in economics and business. Keywords : Education, Financial Literacy, Gen Z